Tierra y libertad : land, liberty, and Latino housing - Bender, Steven (Citizenship and migration in the Americas., 2010)
One of the quintessential goals of the American Dream is to own land and a home, a place to raise one's family and prove one's prosperity. Particularly for immigrant families, home ownership is a way to assimilate into American culture and community. However, Latinos, who make up the country's largest minority population, have largely been unable to gain this level of inclusion. Instead, they are forced to cling to the fringes of property rights and ownership through overcrowded rentals, transitory living arrangements, and, at best, home acquisitions through subprime lenders. In Tierra y Liber.